2011
DOI: 10.1128/aac.01302-10
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Posaconazole Levels in Toenails of Adults with Onychomycosis following Oral Treatment with Four Regimens of Posaconazole for 12 or 24 Weeks

Abstract: Pharmacokinetic data from a randomized, parallel-group, multicenter study are presented. Adults with toenail onychomycosis (n ‫؍‬ 146) received posaconazole (100 mg, 200 mg, or 400 mg) once daily (QD) for 24 weeks or 400 mg QD for 12 weeks. The posaconazole concentration in the great toenail exhibited a dose-related increase starting at week 2 for 24 weeks and a mean toenail-to-plasma concentration ratio of approximately 3:1 at the end of treatment for the 400-mg 24-week dose.Posaconazole, a triazole antifunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…12 Previous studies demonstrated adequate skin and nail penetration of posaconazole. [13][14][15] Posaconazole should be administered orally during a high-fat meal and requires, at high-dosage use (600-800 mg/d), monitoring of blood levels (recommended concentration, 1.2-2.0 mg/L) and liver enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies demonstrated adequate skin and nail penetration of posaconazole. [13][14][15] Posaconazole should be administered orally during a high-fat meal and requires, at high-dosage use (600-800 mg/d), monitoring of blood levels (recommended concentration, 1.2-2.0 mg/L) and liver enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of posaconazole within the human dermis is comparable to that in plasma (59). However, in toenails, its concentration is both dose and time dependent, attaining a maximum approximately 3 times greater than that in plasma after 24 weeks of therapy (223). There are no human data for voriconazole, but in guinea pigs, voriconazole skin concentrations are approximately twice those in blood, while in skin microdialysates, the voriconazole concentrations are only 50% of those in blood (224).…”
Section: Skin and Nailsmentioning
confidence: 98%
“…This pattern was not observed in the delayed-release tablet [28] due to the distinct differences in the gastrointestinal drug-delivery features between these two oral formulations. Figure 2 shows posaconazole distribution in various human tissues and fluids after systemic administration [52][53][54][55][56][57][58][59][60][61]. This figure shows that posaconazole accumulates in peripheral tissues, especially in lungs, kidneys, liver, and heart [52,62].…”
Section: Absorptionmentioning
confidence: 99%